PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN MEDIA TIGA DIMENSI PADA MATA PELAJARAN MATEMATIKA POKOK BAHASAN SIFAT-SIFAT BANGUN RUANG KELAS V SDN 1 SUMBERKOLAK KECAMATAN PANARUKAN KABUPATEN SITUBONDO TAHUN PELAJARAN 2013/2014 - Inge Putri Utami; Vidya Pratiwi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2014)
Activities and learning outcomes of students of grade V SDN 1 Source of rejects in the subjects of mathematics is very low. This is because teachers are still using conventional learning model so that the math learning feels monotonous and makes students feel bored. In learning the teacher uses more lectures. Teachers also do not use the media in teaching. This shows that the teacher has not given a concrete picture of the material presented, so the learning is still abstract. In contrast, in the mathematics lesson the subject matter of the waking character of the student space is expected to have a concrete (real) experience. Therefore, teachers need to use the media in implementing learning such as three-dimensional media. Three-dimensional media is a medium that can be observed from any point of view and has dimensions of length, width and height. The use of three-dimensional media can provide a direct or real experience to students.The formulation of the problem in this research are: (1) How is the step of using three dimensional media in mathematics subject matter of the building characteristic of class V SDN (1)SumberKolakAcademic Year 2013/2014, (2) How to increase student learning activity through media usage Three dimensions in the mathematics subject matter the characteristics of class V SDN 1 classroom learning source of 2013/2014?, And (3) How to improve student learning outcomes through the use of three dimensional media on the subject of mathematics subject Class V SDN 1 SumberKolak year lesson 2013/2014.This research was conducted in class V SDN 1 SumberKolak consisting of 26 students. The type of research used is classroom action research conducted as many as two cycles. This research uses the flow of stages that include: the planning stage, the implementation of the action, observation, and reflection. Methods of data are collection through observation, interviews, tests, and documentation. Percentage of student activity in cycle 1 of 56,41% in active enough category while in cycle 2 equal to 71,47% in active category. In the first cycle of student learning result that is complete 57,69% and in cycle 2 result of student learning which is complete equal to 80,76%.The conclusion of this study is the use of three-dimensional media can make students experience increased activity and learning outcomes. The percentage of student activity from cycle 1 to cycle 2 is increased by 15.06%, while the percentage increase of student learning outcome is 23.07%. Therefore the research at SDN 1 Sumberkolak is said to be complete